2018
DOI: 10.1002/lt.24990
|View full text |Cite
|
Sign up to set email alerts
|

Standardized hybrid living donor hemihepatectomy in adult‐to‐adult living donor liver transplantation

Abstract: The aim of this study was to analyze the outcomes of the most updated version and largest group of our standardized hybrid (laparoscopic mobilization and hepatectomy through midline incision) living donor (LD) hemihepatectomy compared with those from a conventional laparotomy in adult-to-adult living donor liver transplantation (LDLT). Of 237 adult-to-adult LDLTs from August 1997 to March 2017, 110 LDs underwent the hybrid procedure. Preoperative and operative factors were analyzed and compared with convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…A report from Kitajima et al, which included 35 cases of hybrid left hepatectomy, described lower operative blood loss, a longer duration of operation, and a lower incidence of postoperative scar discomfort or tightness . Another relatively large comparative study including 66 cases of hybrid left hepatectomy showed lower blood loss with similar incidence of postoperative complications for donor and recipient survival outcomes . In this study, the authors mentioned that the hybrid technique could be a good option for donor hepatectomy in centers where the pure laparoscopic technique could not be applied due to technical difficulties or medical insurance problems while combining the benefit of both the laparoscopic and open approaches .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…A report from Kitajima et al, which included 35 cases of hybrid left hepatectomy, described lower operative blood loss, a longer duration of operation, and a lower incidence of postoperative scar discomfort or tightness . Another relatively large comparative study including 66 cases of hybrid left hepatectomy showed lower blood loss with similar incidence of postoperative complications for donor and recipient survival outcomes . In this study, the authors mentioned that the hybrid technique could be a good option for donor hepatectomy in centers where the pure laparoscopic technique could not be applied due to technical difficulties or medical insurance problems while combining the benefit of both the laparoscopic and open approaches .…”
Section: Discussionmentioning
confidence: 74%
“…(33) Another relatively large comparative study including 66 cases of hybrid left hepatectomy showed lower blood loss with similar incidence of postoperative complications for donor and recipient survival outcomes. (34) In this study, the authors mentioned that the hybrid technique could be a good option for donor hepatectomy in centers where the pure laparoscopic technique could not be applied due to technical difficulties or medical insurance problems while combining the benefit of both the laparoscopic and open approaches. (33,34) Another study compared the perioperative outcomes between a hybrid donor hepatectomy and PLDH including 14 cases of left hepatectomy in the hybrid group and 9 cases of left hepatectomy in the PLDH group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also improve donor outcomes with regard to postoperative pain, reduced length of stay, quality of life, and body image . A step‐by‐step adoption of LADH is advisable to allow team members to master the necessary skills in laparoscopic mobilization, hilum dissection, and parenchymal transection through relatively compromised surgical exposure during the learning curve .…”
Section: Laparoscopy‐assisted Donor Hepatectomymentioning
confidence: 99%